Study the Fungal Leaching Activity in Relation to the Extracellular Protein Secretion on Different Samples from Um Bogma Formation in Gabal Um Hamd, Southwestern Sinai, Egypt - Walaa S. Mohamed; Yehia M. M. Abbas; Amal A. A. Ammar; Sameh H. Negm; Mohamed M. Rezk; Nilly A. Kawady (Sustainable Chemical Engineering, 2025)
Bioleaching is a mining and biohydrometallurgical process used to extract valuable metals from different ores with the help of microorganisms such as fungi. Five fungal isolates were isolated from seven soil samples collected from Um Bogma Formation in Gabal Um Hamd, southwestern Sinai, Egypt, and were coded from W1 to W7, which were classified geologically into three categories as siltstone (W1, W2, W4), dolostone (W5, W6) and grey shale (W3, W7). The isolated fungi were morphologically identified as Aspergillus hollandicus (A. hollandicus), Penicillium citrinum (P. citrinum), Trichoderma harzianum (T. harzianum), Fusarium roseum (F. roseum), and Aspergillus fumigatus (A. fumigatus). The chemical characterization of the studied samples for uranium revealed a wide variation, with values ranging from 20 ppm in W4 to 9,706 ppm in W7. Additionally, the thorium values obtained ranged from 23 ppm in W2 to 122 ppm in W3. The maximum values of Rare Earth Elements (REEs) were recorded as 153 and 33 ppm in W1 and W6, respectively. The bioleaching activity of uranium, thorium, and REEs exhibited wide variation when applied to the studied samples as follows: 53% (W5), 74% (W3), and 55% (W7) (F. roseum), 58% (W3), 49% (W3), and 41% (W3) (A. fumigatus), 60% (W5), 65% (W1), and 76% (W5) (T. harzianum), 64% (W1), 77% (W5), and 89% (W5) (A. hollandicus), and 70% (W1), 88% (W4), and 33% (W1) (P. citrinum), respectively. Furthermore, the extracellular protein secretion played a major role in bioleaching activity, showing a significant increase at the end of each experiment as the maximum level was recorded as 20.1 and 13.8 mg/L for W6 and 11.7, 10.7, and 5.8 mg/L for W5. This may be considered as a defense mechanism of fungi to generate more energy to face the overdose of metals or radiation toxicity and the increase in fungal digestion enzymes may contribute to enhanced bioleaching activity. Consequently, proteins act as a co-factor in the bioleaching process and a protective agent for fungi to survive against exposure to different environmental stresses such as irradiation or radioactive metals.